The Impact of Photoaging on Skin: A Systematic Review Analysis - Muhammad Shanan Asyi; Dedy Syahrizal; Nirwana Lazuardi Sary; Fauzul Husna (Journal of Social Research, 2023)
Aging of the skin is a complex biological process. The process of skin aging can be divided into two categories namely intrinsic and extrinsic aging. Intrinsic skin aging or natural aging is caused by changes in skin elasticity that occur with age. This type of aging cannot be prevented. While extrinsic skin aging is caused by environmental factors such as exposure to solar radiation (photoaging). In this study, the type of research approach used is a type of qualitative research through a literature review. The type of data used is the type of secondary data. Secondary data is a type of data obtained from certain parties or media indirectly, meaning that certain parties become intermediaries where they obtain and record these data beforehand. The aging process of the skin is influenced by intrinsic and extrinsic factors. The extrinsic factor that most influences the aging process of the skin is chronic sun exposure which is called photoaging. Sunlight contains 96% UVA and has the most significant biological effect compared to UVB and UVC. Several factors that affect photodamaging are skin type, pigmentation, and acclimatization. Skin changes that occur in photoaging include the presence of vesicles in the epidermis, reduced Langerhans cells, and enlarged and pale epidermal cells; in the dermis, there is an elastic mass; pigment changes in the form of dotted (irregular pigmentation) and hyperpigmentation.